LEADING TO LEAD: PRINCIPALS’ SITUATIONAL LEADERSHIP AND ITS INFLUENCE ON TEACHER LEADERSHIP - Ja’afar, Jahlilawati; Adnan, Ahmad Amri Zainal (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Leadership in educational institutions significantly shapes teacher performance, student achievement, and overall school effectiveness. This conceptual study explores the relationship between principals’ situational leadership styles and secondary school teacher leadership in Malaysia. Guided by Hersey and Blanchard (1988) situational leadership model, comprising directing, coaching, supporting, and delegating. The study examines how adapting leadership styles to teacher readiness can enhance motivation, professional commitment, and school climate. A systematic literature review was conducted using secondary sources such as indexed journal articles, academic books, educational reports, and Malaysian Ministry of Education policy documents. Data were retrieved from Scopus, Web of Science, ERIC, and Google Scholar using relevant keywords. Content analysis and thematic synthesis were applied to organise findings according to the four leadership dimensions, leading to a proposed conceptual framework. Results indicate that each style uniquely influences teacher leadership: the directing style benefits new teachers, guiding develops skills and confidence, supporting fosters innovation, and delegating strengthens experienced teachers’ autonomy. Flexible adaptation of leadership styles was found to boost motivation, reduce work-related stress, and cultivate a positive school climate. This study contributes in three main ways: academically, it enriches the body of Malaysian educational leadership literature; for the education sector, it offers training guidelines for principals to tailor leadership styles to teacher maturity; and nationally, it supports the Malaysian Education Blueprint (MEB) by enhancing teacher leadership and educational competitiveness.